Parental behavior of Lynx lynx and Puma concolor: insights from offspring rearing in captivity - Ulitina, Oksana M.; Antonenko, Tatiana V.; Nosova, Marina N.; Glukhova, Daria (Altai State University, 2024)
Animal behavior can serve as an important indicator of welfare for zoo inhabitants. The maternal behaviors exhibited by lynx and puma in captivity are crucial not only for the survival and well-being of their cubs but also provide valuable insights for species conservation programs. We analyzed the motor activity of a male and female Siberian lynx and a male and female puma during the period when they were raising their kittens, which had not yet left the shelter at the time of observation. Our ethological monitoring revealed both similarities and differences in behavior across species and sexes. We found that males of both species exhibited passive behaviors more frequently than females. Overall motor activity was higher during the evening observation periods. Notably, the male lynx spent significantly less time in the shelter compared to the other studied animals, likely due to his close cohabitation with the female and their kittens. In contrast, the male puma was kept nearby but separately from the female and her offspring. Abnormal behaviors were observed in nearly all animals, except for the female lynx. The female puma exhibited the highest level of abnormal activity, frequently carrying her kitten in her mouth for extended periods, which suggests a high level of stress. The intraspecific Shorygin indices of behavioral similarity between male and female lynxes and pumas were relatively low, at 42% and 45%, respectively. In comparison, our previous research indicated that the behavioral similarity index between male and female Eurasian lynxes without offspring was 87%. This suggests that the presence of kittens significantly increases the differences in time budgets between males and females.